Effects of Whole-Body Stretching Exercise during Lunch Break for Reducing Musculoskeletal Pain and Physical Exertion among Healthcare Professionals - Raee Saeed Alqhtani; Hashim Ahmed; Adel Alshahrani; Abdur Raheem Khan; Ashfaque Khan (Medicina, 2023)
Background and Objectives: To investigate the effect of whole-body stretching (WBS) exercise during lunch break for reducing musculoskeletal pain and physical exertion among healthcare professionals. Methods: Full-time healthcare professionals working in hospitals with more than one year of experience were invited to participate. Sixty healthcare professionals (age 37.15  ±  3.9 Years, height 1.61  ±  0.04 m, body mass 67.8  ±  6.3 kg, and BMI 26.5 ± 2.1 kg/m2) participated in this single-blinded, two-arm randomized controlled trial (RCT). Participants were divided into WBS (n = 30) and control (n = 30) groups. The WBS group performed a range of stretching exercises targeting the entire body during a lunch break period for 3 times a week for 6 weeks. The control group received an education program. Musculoskeletal pain and physical exertion were assessed using the Nordic musculoskeletal questionnaire and Borg rating of perceived exertion scale, respectively. Results: The 12-month prevalence of musculoskeletal discomfort among all healthcare professionals was highest in the low back region (46.7%), followed by the neck (43.3%), and then the knee (28.3%). About 22% of participants said that their neck discomfort impacted their job, while about 18% reported that their low back pain impacted their job. Results indicate that the WBS and education program had a beneficial impact on pain and physical exertion (p < 0.001). When comparing the two groups, the WBS group experienced a significantly greater decrease in pain intensity (mean difference 3.6 vs. 2.5) and physical exertion (mean difference 5.6 vs. 4.0) compared to an education program only. Conclusions: This study suggests that doing WBS exercises during lunchtime can help lessen musculoskeletal pain and fatigue, making it easier to get through the workday.